Pelatihan Pembuatan Yoghurt dari Susu Bubuk Instan Full Cream pada Ibu-Ibu Kota Pelangi di Pancoran, Jakarta Selatan - Cempaka, Laras; Asiah, Nurul (LPkM Universitas Bakrie, 2020)
Yogurt is a beverage made from milk which is fermented using lactic acid bacteria. Generally the milk used is fresh milk. Yogurt is the beverage product chosen because of its distinctive taste and its functional. Products that are liked by all ages are not impossible to replace the current drinks that are popular on the market, such as coffee, milk, and tea. So it has the potential to be produced by SMEs. However, Pelangi City SMEs located in an urban area is quite difficult to get raw material for making yogurt, namely fresh milk because it is far from the livestock area. Though these SMEs are in a strategic environment in the big city: D.K.I Jakarta. Therefore, an alternative raw material for fresh milk is needed, namely instant milk powder. This instant milk powder is very easy to find on the market and has a long shelf life thereby reducing the risk of loss. Even so yogurt made from instant milk powder is no less competitive with yogurt from fresh milk. This training was conducted in 2 stages: lecturing and the practice of making yogurt. The prepared yogurt samples were created with different topping and flavoring, the making yogurt begins with pasteurizing milk then adding bacterial culture and incubated within 12-14 hours. This training is not only process abilities that participants need to have but also knowledge of the fermentation process and microbiological aspects that need to be understood, so that the products produced can be of good quality.